PERENCANAAN DAN PENGENDALIAN KAPASITAS PRODUKSI PRODUK RAKITAN RADIO TIPE SOUNESS SNI 4250 - Matondang, Abdul Rahim; Widodo, Widodo (Jurnal Sistem Teknik Industri, 2018)
Production system take an important role in industries, especially in manufacturing industries. This role determine the keys of successful company. Production process is an activity which produce finished product from raw material that involve machine, energy, and technique knowledge. Production process is real activity and can be seen by human being. The problems those always be faced in indutries management’s are the arrangement of production schedule, such lack of inventory or overstock once the settlement of production process isn’t on time. Production planning and control is activity to determine what product that will be produced, how many product that will be produced and how many labors needed in production processes. By using production planning and control’s method, those problems can be minimalized. Aggregate planning is one of production planning a.nd control’s method. By using this method, production planning could be done by using unit of replacement product so that the output of this planning isn’t declared in individual product. So, the output of aggregate planning isn’t planning in form of individual product but aggregate’s product. There are some strategies on aggregate planning such as pure strategy on aggregate planning and mixed strategy on aggregate planning. In this research, method of aggregate planning that used is optimization approach by linier rule. This method used to make long term planning and middle term planning. Long term planning consists of product forecasting and aggregate planning. The middle term planning consist of master production schedule and rough cut capacity planning. The result of this research is capacity needed and capacity available to determine which work center is drum and which isn’t. Conclusion of this research that capacity of each work center in perioad january to december 2018 is non drum. This indicate the good scheduling in capacity planning.